Penguatan Nilai Budaya Lokal melalui Edukasi Ritual Pakon bagi Generasi Muda di Desa Lenek - Mohamad Yudisa Putrajip; Ashar Banyu Lazuardi; Muhammad Nasir; Azril Irzam (CV. Global Cendekia Inti, 2026)
The Pakon ritual is one of the local cultural practices of the Sasak community in Lenek Village, carrying strong social, spiritual, and cultural values. In recent years, its continuity has faced growing challenges due to social change, modernization, and shifting perspectives among younger generations. This study aims to examine efforts to strengthen local cultural values through Pakon ritual-based education for youth. A qualitative approach was applied using descriptive methods, including observation, interviews, and documentation studies. The findings reveal that culture-based education through the Pakon ritual helps deepen young people’s understanding of their local identity, increases appreciation for cultural heritage, and fosters a collective awareness to preserve traditions. It also creates a space where traditional values can meet and adapt to the realities of modern life experienced by the younger generation.